Method engineering for web information systems development: Challenges and issues - SIAU, Keng (Institutional Knowledge at Singapore Management University, 1998)
Despite the rapid advancement of technology in the last few decades, accurate, on-time, and on-budget completion of information systems development projects is still a vision rather than a reality. The software crisis is still very much alive almost forty years after it was first defined. The sudden popularity of Internet and electronic commerce pose a new challenge to the software engineering community. With the increasing importance of electronic commerce and $3 billion in sales expected to take place over cyberspace by the year 2000, organizations will be competing to design and develop web-based applications. However, existing information modeling methods might not be suitable for supporting such activities. This paper looks at some of the challenges and issues involved in engineering methods for analysis and design of web-based information systems. The paper then proposes the use of a popular model in human-computer interaction, GOMS, as one of the potential tools in designing web-based applications.